DEVELOPMENT OF A LEARNING MANAGEMENT PLAN USING THE DESIGN THINKING PROCESS FOR LOWER SECONDARY STUDENTS TO ENHANCE INTEGRATED PROBLEM-SOLVING COMPETENCY IN CONJUNCTION WITH THE SUSTAINABLE USE OF GENERATIVE ARTIFICIAL INTELLIGENCE NABON SCHOOL NAKHON SI THAMMARAT - Boonjit, Wisitsak; Wannasawade, Wannachai (Journal of MCU Nakhondhat, 2025)
The objectives of this research were: 1) To develop and evaluate the quality of learning management plans using design thinking processes for lower secondary school students, and 2) To assess students' integrated problem-solving competencies combined with sustainable creative artificial intelligence (AI) after implementing the developed learning management plans. This research employed an experimental and qualitative research design. The participants consisted of 44 students in grade 9 at Nabon School, selected using simple random sampling through a lottery method. The research instruments included learning management plans based on design thinking processes and an evaluation form for integrated problem-solving competencies combined with sustainable creative AI. Statistical analyses conducted in this research were mean and standard deviation. The research findings indicated that the developed learning management plans were rated at the highest quality level regarding content validity, with an average score of 4.58, and at the highest level of appropriateness, with an average score of 4.64. Furthermore, the overall evaluation of students' integrated problem-solving competencies combined with sustainable creative AI was at an excellent level, achieving an average score of 56.91, equivalent to 94.85%. Students scored full marks (100%) in designing problem-solving methods. Additionally, their competency scores for problem understanding reached 98.48%, while scores for problem-solving method exploration reached 97.73%. Overall, the evaluation reflected the effectiveness of integrating design thinking processes with AI in enhancing sustainable creative problem-solving competencies. This study thus provided significant insights into developing learning approaches aligned with 21st-century educational demands and promoting students' competencies related to sustainability.